Modified Ginzburg-Landau equation and Benjamin-Feir instability - Kengne, E. (Нелінійні коливання, 2003)
In this paper the modulated wave train in nonlinear monoinductance LC circuit is studied. Using the
method of multiple scales in general form, we establish that the evolution of nonlinear excitations is
governed by what we called the Modified Ginzburg – Landau Equation (MGLE). Benjamin – Feir instability for the MGLE is analyzed Вивчається проходження модульованих хвиль у нелiнiйному моноiндуктивному LC-ланцюзi. З
використанням методу кратних шкал отримано, що еволюцiя нелiнiйних збуджень описується
за допомогою рiвняння, яке ми називаємо модифiкованим рiвнянням Гiнзбурга – Ландау (МРГЛ).
Аналiзується стабiльнiсть МРГЛ у сенсi Бенджамiна – Фейра.